Zero average current error control methods for bidirectional AC-DC converters. - Borle, Lawrence J. (Curtin University, 1999)
This thesis is concerned primarily with the optimization of the current regulation in bi-directional ac-dc power converters through the use of appropriate current control methods. Following a review into prior current control technology, current control methods which attempt to achieve Zero Average Current Error (ZACE) in each switching period are presented. A ZACE controlled converter offers independent real and reactive power flow control with negligible low order current harmonics, a relatively narrow switching frequency band, and relative immunity to power circuit parameter variations, including DC link or AC line voltage harmonics. ZACE and other desirable characteristics in a current control method are discussed. The single phase ac and dc ripple current is characterized.Two new types of ZACE current control techniques for directly controlling the inductor current in switched power converters are introduced in this thesis together with variations for certain applications. Slope-generated hysteresis (SGH), the first to be developed, is a hysteresis method which uses the slopes of the current error signal alone to generate a hysteresis band which will result in a fixed switching frequency. Slope-generated hysteresis-clock (SGHC) is presented as an alternative with a dual clock to force a narrow switching frequency band.Ramptime current control is the second type of ZACE current control presented. Developed as an improvement over SGH, ramptime produces ZACE in each switching period by using the timing of a previous switching instant relative to the coincident previous current error signal excursion time to determine each switching instant. The digital current error polarity signal is the only variable input required to produce a pwm output.Variations of ramptime current control are also presented. Polarized ramptime is a subset of ramptime which maintains a narrow switching frequency band despite switching delays. Dual ramptime is the final enhancement of ramptime where two polarized ramptime regulators are used together to provide the appropriate choice between full-bridge and half-bridge switching in a single phase current controlled full-bridge voltage source inverter with the ac ripple current minimized without compromising the transient response. Using this technique, excellent fidelity and a narrow switching frequency band are demonstrated.The ZACE current control techniques are applied to a three phase voltage source inverter. A "standing phase" system of control for a three wire, three phase inverter is chosen over individual phase control since only two current regulators are required to control two decoupled current error signals, and the effective switching frequency is reduced by one third.The new ZACE methods are found to compare favourably in simulation to existing linear and hysteresis type current control techniques. SGH current control has equivalent fidelity to any other hysteresis control in delivering the reference current waveform, but is prone to noise in the hysteresis band determination requiring filtering. This, combined with the effect of switching delays compromises the narrowness of the switching frequency band. SGHC current control is also prone to noise in the generation of the hysteresis band, and results in a decrease in the fidelity of reproduction of the reference waveform. Ramptime current control is a robust technique, largely immune to power circuit parameter and voltage variances, with good fidelity and a relatively narrow switching frequency band. Polarized ramptime current control is shown to produce excellent fidelity with a narrow switching frequency band.The operation of the ZACE methods in single and three phase prototype converters is demonstrated. A field installation of a grid-connected ramptime current controlled converter is shown to source 20 kW of real power onto the grid from a photovoltaic array with a maximum power point tracking control, while independently providing grid voltage support through reactive power control.The effect of the synchronization of the current regulators on the ac and dc current ripple are presented. Synchronized polarized ramptime regulators are shown to produce the minimum ripple current in simulation and in the prototype operation.ZACE current control techniques, and ramptime and polarized ramptime in particular, are presented as a significant contribution to the control of current in power electronic converters.